FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN (STUDI KASUS DALAM DIVISI FINANCE DAN ACCOUNTING PT. MULIA CEMERLANG ABADI MULTI INDUSTRY) - Eistiana, Indri; Destiningsih, Rian (Universitas Indo Global Mandiri Palembang, 2021)
Increased employee performance can be achieved through improvements in the working environment as well as satisfaction in compensation. Companies should pay more attention to factors for employee performance in the company. The focus on this research is to look at the relationships of the working environment as well as compensation to employees performance. Using qualitative method of descriptive and do dissemination questionnaire. Respondents were investigated by 16 total employees in the Finance and accounting division of PT. Mulia Cemerlang Abadi Multi Industry. The study was treated with validity testing and reliability testing. The results of the research in 2020 at PT. Mulia Cemerlang Abadi Multi Industry State if the work and compensation environment has a relationship to the increase in employee performance.